(untitled) (Research, Society and Development, 2022)
Oral rehabilitation seeks aesthetic and functional outcomes, and can make use of multidisciplinary dentistry, involving several specialties to treat clinical cases. Therefore, depending on the situation, maneuvers in the periodontal tissue can be performed in procedures involving ceramic laminates. The article aims to present a literature review on the association between periodontal biotype and dental prosthesis. The literature is confident in stating that the periodontal biotype can directly influence oral rehabilitation with fixed prostheses, whether in the short or long term. In prosthetic treatments, it is necessary to evaluate the gingival contour (zenith), in order to have a natural reproduction of the prosthesis-gingival interface. Favoring an appropriate proportion between height and tooth width, which can be seen more in the anterior region. In order to obtain a satisfactory result in oral rehabilitation, it is essential to have an association between the set: patient’s face, smile line, lips, periodontal tissue and the prosthesis. Especially in complex rehabilitations, there is a need for the dentist to perform a multidisciplinary approach, making an integrated planning. However, it is still a clinical challenge to obtain an appropriate interaction between fixed prostheses and periodontal biotype, seeking harmonious treatments.